2022
DOI: 10.1155/2022/5660462
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic Pain Relief after Surgical Neurolysis in Patients with Traumatic Brachial Plexus Injuries: A Preliminary Report

Abstract: Objective. To evaluate the usefulness of surgical neurolysis for neuropathic pain relief in patients with posttraumatic brachial plexus injury (BPI). Methods. A prospective, longitudinal, nonrandomized, self-controlled before and after study was performed to evaluate the pain changes according to their intensity using the Visual Analogue Scale (VAS), and the sensory recovery after surgery using the British Medical Research Council (BMRC) scale for sensory recovery. To establish significant changes, a paired T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(33 reference statements)
2
1
0
Order By: Relevance
“…The results of the studies are encouraging, showing a decrease between 59% and 78% according to the VAS scale [8,16,32], these being very similar to those observed in the present study (84%). Based on the results recently published in our last article on the use of decompression for pain relief, we decided to exclude those patients who showed signs of nerve transection in the preoperative electrophysiological analysis or during the surgical procedure [32]. Conversely, Morgan R et al [8] reported motor recovery after the use of surgical decompression in trauma patients [8], these results are relevant, so we decided exclusevely to disccuss the clinical outcomes of these patients in motor terms in another article with a systematic review of the literature (on published).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the studies are encouraging, showing a decrease between 59% and 78% according to the VAS scale [8,16,32], these being very similar to those observed in the present study (84%). Based on the results recently published in our last article on the use of decompression for pain relief, we decided to exclude those patients who showed signs of nerve transection in the preoperative electrophysiological analysis or during the surgical procedure [32]. Conversely, Morgan R et al [8] reported motor recovery after the use of surgical decompression in trauma patients [8], these results are relevant, so we decided exclusevely to disccuss the clinical outcomes of these patients in motor terms in another article with a systematic review of the literature (on published).…”
Section: Discussionsupporting
confidence: 90%
“…However, the usefulness of surgical decompression to reduce pain in patients with a chronic BPI associated with compressive neuropathy has recently been suggested, a phenomenon previously explained (development of fibrosis secondary to trauma that conditions ischemia and upregulation of inflammatory cytokines) [4,27]. The results of the studies are encouraging, showing a decrease between 59% and 78% according to the VAS scale [8,16,32], these being very similar to those observed in the present study (84%). Based on the results recently published in our last article on the use of decompression for pain relief, we decided to exclude those patients who showed signs of nerve transection in the preoperative electrophysiological analysis or during the surgical procedure [32].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…(6) If feasible, blinding will be implemented for patients, treating physicians, and the individuals performing statistical analyses. (7) Potential sources of bias, such as demographic characteristics, mechanism of injury (etiology), severity, and extension of the injury, interval between injury and surgery [34], location of the injury, preservation of muscle trophism, and integrity of muscle/nervous structures defined through electromyographic and nerve conduction analysis [2,35], will be carefully considered and addressed in the study design.…”
Section: Further Considerationsmentioning
confidence: 99%
“…However, a recent systematic review comparing motor outcomes of various surgical techniques for brachial plexus injuries demonstrated that neurolysis presented the highest proportion of motor recovery (85%) compared to other techniques, which showed recovery rates below 73% [5]. Conversely, a study by Morgan R. et al (2020) evaluating 21 patients with distal brachial plexus injury who underwent surgical neurolysis and open fasciotomy observed an improvement in the motor component, and other studies have shown effectiveness in pain relief and sensory recovery [6,7]. Although the study by Morgan R. et al did not evaluate surgical neurolysis as an isolated technique, it provides valuable insights into its potential usefulness.…”
Section: Introductionmentioning
confidence: 99%